TB survivors: why curing TB is sometimes not enough - E. Pontali; R. Centis (IJTLD Open)
It is now well understood that the effect of TB does not always end when a patient completes a successful course of treatment. Successful treatment is by definition a microbiological cure, but people may continue to suffer the consequences of TB for months or years after treatment. For example, ongoing health challenges can present in the form of post-TB lung disease (PTLD), and there is a high incidence of TB-related symptoms associated with disability in other domains. We discuss an article in this issue of the Journal that explores the experiences of adult TB survivors, which further expands our understanding of this condition.